Endovenous laser coagulation of varicose veins: evolution continues - V. P. Minaev; V. Yu. Bogachev; K. A. Kaperiz (Амбулаторная хирургия)
The article discusses the evolution of the endovenous laser ablation technique for the treatment of varicose vein disease of lower extremities. The history of studies aimed at improving the endovenous laser ablation is provided. The authors described the features of endovenous laser ablation with wavelengths from λ = 0.445 to 1.94 µm, alongside with edge- and radial-emitting working fibers, as well as fibers with radiation absorption at its distal end. The physical and biophysical mechanisms of the most popular to-date method for outpatient treatment of varicose vein disease of lower extremities are reviewed. The propagation process of laser radiation in the scattering medium is described, and the important role of the radiation scattering effect on the depth of its penetration into biological tissues is shown. The processes that take place during endovenous laser ablation are considered. The difference in physical processes that take place during the use of laser radiation mainly absorbed by hemoglobin (hemoglobin-absorbed range) and by water (water-absorbed range) is described. Expedience of simulating the processes that take place during endovenous laser ablation with the use of blood plasma has been substantiated. The blood plasma simulation demonstrated the decisive action of laser-induced boiling on thermal damage to the vein wall, which causes its fibrous transformation. It has been shown that the use of radial-emitting fibres during intense boiling generates steam bubbles around the site of radiation coupling. The contents of such steam bubbles do not absorb radiation, which thus reaches the venous wall, causing its symmetrical thermal damage. The advantages of using water-absorbing radiation with a wavelength of λ = 1.94 µm in conjunction with a radial-emitting fibre have been substantiated.